Manajemen Media Relations di Bidang Humas Polda Jabar dalam Meningkatkan Citra Positif - ahmad, muhamad muksin; Mukarom, Zaenal; Rosyidi, Imron (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2024)
This study aims to determine the Public Relations Division of the West Java Regional Police in managing relations with the media, developing media relations policy strategies and building networks with the media as an effort to enhance a positive image. The method used in this study is a qualitative study method in which this study describes the media relations management strategy carried out by the Public Relations Division of the West Java Regional Police in the form of a description. The results of this study illustrate that the media relations management strategy used by the Public Relations Division of the West Java Regional Police in building relations with the media as an effort to build a positive image is by carrying out partnerships and managing relations with the media, both task relations and personal relations which converge in it includes a combination of print media, electronic media, and online media by considering the aspects of objectivity, transparency, accountability, and participation.